DETERMINATION OF THE USED ADDITIVES AND THEIR CORRECT DECLARATION, IN ACCORDANCE WITH THE LEGISLATION FOR MEAT PRODUCTS - Silovksa NIkolova Aleksandra; Belichovska Daniela (Knowledge International Journal, 2020)
Meat is dominant in the life of humans, both in its fresh and in its processed form. The contemporary and modern production of processed meat cannot be imagined without the use of additives. They are used under specified conditions, for clearly defined reasons, in clearly determined products, as well as in clearly defined amounts. The number of additives used in the meat processing industry is large. In meat products, the following functional classes of additives are usually added: dyes, preservatives, antioxidants, emulsifiers, acid regulators, acids, stabilizers, thickeners and gelling agents, packaging gases, etc. This research covers a random selection of 300 products sold on the market and the following numbers were obtained: meat preparations - 18 (6.00%)samples , fermented permanent sausages - 46 (15.33%) samples , boiled finely chopped sausages - 54 ( 18.00%) samples , boiled fragmented meat sausages - 42 (14.00%) samples, semi-permanent coarsely chopped sausages - 40 (13.33%) samples , fresh sausages - 20 (6.67%) samples , semi-permanent cured meat products – 48 (16.00%) samples and permanent cured meat products - 32 (10.67%) samples . The survey showed that in 47 (16%) samples, the declaration of the additives was incorrect, i.e. only the E-numbers were listed, but not the additive category. Furthermore, in some samples the special name of the additive was listed, but not its category. This is contrary to applicable law. The added additives in the meat processing are in accordance with the legislation. The most widely used and most common additives in the meat products are the nitrites. However, we cannot deny the fact that the use of nitrites has an adverse effect on the consumers’ health. Meat processors need to consider using alternative sources of nitrites, in order to offer the consumers natural meat products, which would arouse greater interest.
Keywords: additives, meat products, declaration, use, legislation